Inflow and Outflow of Oil Revenues: Scenarios for National Development Fund of Iran(NDFI) - Seyed Hossein Mirjalili; Salim Karimzadeh (Iranian Economic Review, 2021)
Resource-rich developing countries are forced by economic fluctuations due to international commodity price movement. One way to reduce the volatility adverse effects is to establish institutions such as Sovereign Wealth Fund. However, the way this fund is managed is important. Iran, as a resource-rich developing country, suffers from economic fluctuations. To manage resource revenues, National Development Fund (NDF) has been established. In this paper, using DSGE model, we examined different scenarios for managing fund resources. A scenario, without any stabilizer Fund and two different scenarios for National Development Fund. In the second scenario, NDF has a role like the one in Sixth Development Plan. In the third scenario, all oil revenues are deposited to NDF and a part of the fund as much as interest rate in the OECD countries plus 70% of long-run oil revenues invested in the economy. The Results indicated that the management of oil revenues by the Fund, in which the inflow of oil revenues into the economy follows the commitment, is an appropriate policy to reduce the economic fluctuations in Iran.
Keywords: 330; Economic Fluctuations; Fiscal Policy; DSGE; Iranian Economy; Macroeconomics; National Development Fund (NDF); Oil Revenue